2020
DOI: 10.1186/s13019-020-1061-1
|View full text |Cite
|
Sign up to set email alerts
|

Giant unruptured sinus of Valsalva aneurysm successfully managed with valve-sparing procedure – a case report

Abstract: Background: Sinus of Valsalva aneurysm (SVA) is an uncommon cardiac anomaly, with an incidence of less than 1% of open heart surgery cases. Its evolution is most frequently silent, being found incidentally or discovered in the event of its acute rupture. Non-ruptured giant SVAs may cause unusual clinical manifestations, as a consequence of their protrusion into the heart chambers or compression of the coronary vessels and are frequently associated with aortic insufficiency of various degrees of severity. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…2 Nonruptured aneurysms are mostly asymptomatic but can cause dyspnea, angina, or arrhythmias. 3 Patients can present with symptoms similar to acute coronary syndromes when the coronary arteries are obstructed, as in this case. The most fatal complication is acute rupture.…”
Section: Discussionmentioning
confidence: 91%
“…2 Nonruptured aneurysms are mostly asymptomatic but can cause dyspnea, angina, or arrhythmias. 3 Patients can present with symptoms similar to acute coronary syndromes when the coronary arteries are obstructed, as in this case. The most fatal complication is acute rupture.…”
Section: Discussionmentioning
confidence: 91%
“…As reported by Wang et al [4][5][6] , residual AI has a poor prognosis often requiring aortic replacement or valvuloplasty, or aortic root replacement. Polos et al 7 performed a valve-sparing root reconstruction procedure(remodeling technique)for an SVA and Carlotta et al 8 conducted an aortic valve repair using a hemi-remodeling technique. However, Wingo et al 9 and Abraiov et al 10 reported in a retrospective study that good results can be obtained by patch closure or aneurysm plication.…”
Section: Discussionmentioning
confidence: 99%
“…Authors' information 1 Department of Ultrasonography,Yanbian University Hospital,Yanji 133000, Jilin,China. 2 Nursing Department,Yanbian University Hospital,Yanji 133000, Jilin,China.…”
Section: Declarations Ethical Approval and Consent To Participatementioning
confidence: 99%
“…Aneurysms of the sinuses of Valsalva are de ned as dilatation of the aortic root region between the aortic annulus and the sinotubular junction.They may be congenital, especially secondary to connective tissue disorders or in conjunction with congenital cardiac defects, or acquired such as secondary to infections or trauma [1].Sinus of Valsalva aneurysm is just an uncommon cardiac anomaly,a congenital or acquired cardiac defect that is present in roughly 0.09% of the general population.With an incidence of less than 1% of opening heart surgery cases.The gold standard treatment for Sinus of Valsalva aneurysm consists of complete replacement of the aortic root and valve [2,3].Aortic sinus aneurysm is a rare and usually asymptomatic lesion.Rupture leads to chest tightness and dyspnea, suggesting left or right heart failure. Rupture of Valsalva sinus remains a very rare and deadly complication of Valsalva sinus aneurysm with a high mortality rate.Surgery is the primary treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%